Pengaruh Ukuran Perusahaan, Ratio Kecukupan Modal, Dana Syirkah Temporer, dan BOPO Terhadap Profitabilitas Bank Syariah Di Indonesia - Hananto, Bernad; Amijaya, Sutrisna (DPPM Universitas Pelita Bangsa, 2021)
Profitability is an important factor in a business entity, the management of an Islamic bank has an interest in maximizing the use of its resources, in this case how Islamic banks manage their assets in order to obtain adequate profits which in turn increase the value of shareholders. The research was carried out in order to prove that the size, company size, capital adequacy ratio, temporary syirkah funds and BOPO could affect the profitability of Islamic banks in Indonesia in this study proxied by the ROA ratio as a measure of financial performance, both jointly and partially by using the panel data regression method with the Eviews9 application. The results of this study indicate that simultaneously, or partially Total Assets and Capital Adequacy Ratio (CAR) have a positive effect on profitability and Temporary Syirkah Funds simultaneously have no effect on profitability, but partially the Temporary Syirkah Funds have an effect on profitability, while BOPO simultaneously has an effect on profitability negatively on profitability, while partially BOPO has no effect on profitability.